2001
DOI: 10.1590/s0004-282x2001000500014
|View full text |Cite
|
Sign up to set email alerts
|

Tics and Tourette syndrome: clinical evaluation of 44 cases

Abstract: We evaluated 44 patients with tics and Tourettes syndrome (TS) emphasising the age of onset of symptoms, sex, classification and localization of tics, associated symptoms and signs and comorbidities. Thirtythree patients (75.2%) had TS defined criteria whereas 10 (22.7%) had chronic motor and/or vocal tics. Simple motor tics were found in 43 cases (97.7%), mainly affecting the eyes (43.2%), mouth (43.2%), face (34.1%). Simple vocal tics occurred in 33 (75%). Coprolalia was found in just 6 cases (13.6%) and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…In 16 uncontrolled studies in specialist centers examining mood changes among 5409 GTS patients, depressive symptomatology, dysthymia, mood swings and/ or MDD, or depressive illness was found in 13-76%. The main diagnosis was MDD [23,27,[31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Comorbidity and Psychopathologymentioning
confidence: 99%
“…In 16 uncontrolled studies in specialist centers examining mood changes among 5409 GTS patients, depressive symptomatology, dysthymia, mood swings and/ or MDD, or depressive illness was found in 13-76%. The main diagnosis was MDD [23,27,[31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Comorbidity and Psychopathologymentioning
confidence: 99%
“…In a recent study, coprolalia was suggested to be a potential risk factor for malignant evolution of GTS1 and, evidently, has an important social and professional impact. The frequency of this symptom is estimated to range from 8% to 26% depending on the study population 2, 3. The pathophysiology of coprolalia is poorly understood.…”
mentioning
confidence: 99%
“…The estimated prevalence of the disease ranges from 1 to 10 per 1000 children and adolescents, being associated with various comorbidities such as attention deficit and obsessive-compulsive disorders 1,2 . These comorbidities have been reported in various series of Brazilian patients in the literature [3][4][5] . It is believed nowadays that Ts has significant genetic determinant, and several candidate genes have been described.…”
mentioning
confidence: 76%